Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1967
DOI: 10.1149/1.2426648
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition of Coherent Deposits of Refractory Metals

Abstract: After observing an irreversible step in the electrode process in all cases of coherent deposition of metals from molten fluorides, a chronopotentiometric study of the normalKCl‐normalLiCl‐K3MoCl6 system which produces coherent molybdenum deposits was undertaken. It was found that in this case also, the electrode process was irreversible at 600 °C, a temperature at which coherent deposits are produced, and became more reversible as the temperature increased. The irreversible behavior of the electrode and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
26
0

Year Published

1970
1970
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(28 citation statements)
references
References 9 publications
2
26
0
Order By: Relevance
“…III) species diffusion coefficients in LiCl-KCl-CsCl melt obtained here are in good agreement with reported in the literature for LiCl-KCl eutectic, 8±0.5·10 -6 cm 2 /sec at 773 K (16) and 1.43·10 -5 cm 2 /sec at 873 K(22).…”
supporting
confidence: 91%
“…III) species diffusion coefficients in LiCl-KCl-CsCl melt obtained here are in good agreement with reported in the literature for LiCl-KCl eutectic, 8±0.5·10 -6 cm 2 /sec at 773 K (16) and 1.43·10 -5 cm 2 /sec at 873 K(22).…”
supporting
confidence: 91%
“…Similar behavior was observed by Senderoff and Mellors, who attributed it to disproportionation to Mo 5. and molybdenum metal (59). Difficulties were encountered because of the instability of Mo 3 § ion in the melt; the concentration was continuously decreasing, and a black precipitate appeared in the melt.…”
Section: Iron In Lici-mentioning
confidence: 99%
“…Chloride melts containing Mo (III) are unstable and the concentration of the MoCl 6 3-species present gradually decreases over time (23,24). This drop in Mo(III) concentration is generally explained by the disproportionation of dissolved molybdenum(III) chloride to molybdenum metal and volatile molybdenum(V) chloride: 5 MoCl 6 3-→ 2 Mo + 3 MoCl 5 + 15 Cl - [1] Senderoff and Mellors also suggested that in highly concentrated melts molybdenum dimeric species can be formed (23):…”
Section: Introductionmentioning
confidence: 99%